Post-operative ocular infection due to Streptococcus dysgalactiae subspecies equisimilis - Kaliamurthy, Jayaraman; Cuteri, Vincenzo; Jesudasen, Nelson; Salman, Amjad; Thomas, Philip A; Preziuso, Silvia (The Journal of Infection in Developing Countries, 2011)
Ocular infections due to Streptococcus dysgalactiae subsp. equisimilis are rare. In the present report, three patients with a history of uncomplicated small incision cataract surgery with intraocular lens implantation developed exogenous endophthalmitis due to Streptococcus dysgalactiae subsp. equisimilis. The identification of the organisms was confirmed by PCR for a 16S rRNA sequence specific to the species S. dysgalactiae. Intravitreal treatment of cefazolin and amikacin, in addition to topical ofloxacin and tobramycin, resulted in resolution of infection in all three patients. Our reports indicate the importance of bacterial culture and molecular identification in the diagnosis of S. dysgalactiae subsp. equisimilis infection in the eye.